2014
DOI: 10.5535/arm.2014.38.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Associating Factors Regarding Nasogastric Tube Removal in Patients With Dysphagia After Stroke

Abstract: ObjectiveTo demonstrate associating factors regarding nasogastric tube (NGT) removal in patients with dysphagia after stroke.MethodsThis study is a retrospective medical chart review. Patients were divided into non-brain stem (NBS) and brain stem (BS) groups. A videofluoroscopic swallowing study was conducted until swallowing functions were recovered. Initial disease status was measured using the National Institutes of Health Stroke Scale (NIHSS) and the modified Rankin Scale (mRS). Risk factors related to str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 25 publications
4
24
0
Order By: Relevance
“…This study revealed that age, FOIS, and NHISS on admission may be the key individual factors that determine swallowing recovery at day 7, day 14, and day 30 for patients after acute stroke, similar to some previous studies. 30,31 The FOIS is a widely used, reliable and valid outcome parameter to measure a patient's safe and adequate functional oral intake, 24 ranging from 1 (nothing by mouth) to 7 (total oral diet with no restrictions). Galovic et al identified age, stroke sever-ity on admission, lesion location, initial risk of aspiration, and initial impairment of oral intake as variables for predicting the recovery of oral intake and a return to prestroke diet at day 7 and at day 30.…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed that age, FOIS, and NHISS on admission may be the key individual factors that determine swallowing recovery at day 7, day 14, and day 30 for patients after acute stroke, similar to some previous studies. 30,31 The FOIS is a widely used, reliable and valid outcome parameter to measure a patient's safe and adequate functional oral intake, 24 ranging from 1 (nothing by mouth) to 7 (total oral diet with no restrictions). Galovic et al identified age, stroke sever-ity on admission, lesion location, initial risk of aspiration, and initial impairment of oral intake as variables for predicting the recovery of oral intake and a return to prestroke diet at day 7 and at day 30.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, we used FIM, which is strongly correlated with severity at the onset of stroke, as a covariate. On the other hand, a retrospective study indicated that there was no difference in National Institute of Health Stroke Scale scores between the stroke region‐matched patients who achieved full oral intake and those who were dependent on tube feeding . Therefore, stroke region and the severity of stroke should be taken into account in the cohort study investigating prognosis of dysphagia.…”
Section: Discussionmentioning
confidence: 99%
“…The PAS offers the advantage that it takes relatively less time to interpret the scores than other methods and that it exhibits a high inter-rater reliability [ 12 ]. However, previous studies on the PAS were mostly based on nasogastric tube removal, and it was difficult to find a study of gastrostomy tube weaning based on the PAS score [ 13 , 14 ]. In this study, the PAS score was found to be an independent predictive factor, and the PAS was considered a screening test for successful gastrostomy tube weaning.…”
Section: Discussionmentioning
confidence: 99%